Analysis of Grade XI Students’ Misconceptions on Nervous System Material Using Five-Tier Diagnostic Test (5TDT) - Sri Wahyuni Angel Gurning; Ahmad Naharuddin Ramadhan (Jurnal Penelitian Pendidikan, 2026)
The Nervous System is a material in Biology that is abstract and complex, which can lead to misconceptions among students. This study aims to identify the conceptual understanding profile using the Five-Tier Diagnostic Test (5TDT). The analysis includes levels of misconceptions and sources of misconceptions. The research data sources were selected using a purposive sampling technique. The research population consists of a real population, namely all grade XI students of SMA Negeri 3 Semarang, as well as a hypothetical population consisting of individuals with similar characteristics. The results showed that the conceptual understanding profile in the Nervous System of grade XI students' material was still dominated by the lack of knowledge (LK) category. Grade XI students were more likely to experience misconceptions about overgeneralization. The most dominant source of misconceptions came from personal thoughts. Further research is recommended to develop or test the effectiveness of learning models that can improve scientific conception (SC) and reduce lack of knowledge (LK). Furthermore, evaluating the quality and accuracy of learning resources is necessary to minimize the emergence of misconceptions.